STRATEGIC MARKETING MANAGEMENT AND ENROLLMENT SUSTAINABILITY IN ISLAMIC PRIVATE SCHOOLS: A QUALITATIVE CASE STUDY IN THE DIGITAL ERA - Huri, Agus; Pudjaningsih, Wiwik (Information Technology Education Department, 2026)
This study examines how strategic marketing management contributes to enrollment sustainability in Islamic private schools operating in the digital era. It seeks to identify structural mechanisms that influence stable student enrollment beyond short-term promotional efforts. A qualitative case study design was employed using document-based analysis. Institutional strategic plans, marketing records, digital communication archives, and three-year longitudinal enrollment data were systematically analyzed through thematic coding and SWOT-based strategic interpretation. The findings reveal that enrollment sustainability depends on the integration of strategic coherence, analytics-enabled digital marketing, measurable service quality governance, and institutionalized trust mechanisms. Enrollment volatility was linked to campaign-dependent recruitment strategies, strategic–operational misalignment, and the absence of structured performance evaluation systems. At the same time, strong Islamic identity and community trust provided differentiation, but the lack of data-driven governance limited long-term stability. This study advances educational marketing theory by proposing an integrative sustainability model that bridges strategic management, digital transformation, service quality governance, and trust institutionalization in faith-based private schooling contexts.